Can Company Size Moderate Transfer Pricing, Profitability, and Gender Diversity on Tax Aggressiveness? - Lucia Ari Diyani; Huda Aulia Rahman; Muhammad Takrim (JURNAL ONLINE INSAN AKUNTAN, 2025)
Taxes are recognized as one of the largest sources of income for the Indonesian state. Tax revenue comes from the community. Taxes are used by the government to fund state expenditures. Countries with stable economic capacity can be assessed from the achievement of the tax ratio in one period. The need for state revenue makes the government set a tax revenue target every year. This study examines whether company size can moderate the effect of transfer pricing, profitability, and gender diversity on tax aggressiveness. The research population comes from companies of manufacture that went public in the period of 2020-2023. The research sample used was 84 companies with a total data is 336, which were selected by purposive sampling. The method of this study is quantitative with analysis of panel data regression. The outcomes explained that there was a positive effect between transfer pricing and tax aggressiveness, negative effect between gender diversity and tax aggressiveness, while there was no effect between profitability and tax aggressiveness. In addition, company size is proven to be able to moderate the effect of transfer pricing and gender diversity on tax aggressiveness, but is unable to moderate profitability on tax aggressiveness.